Athlete Endorser-Brand Relatedness and Perception of Source Credibility as in Schema Theory - Terason, Sid (Kasetsart Journal of Social Sciences, 2014)
This research investigated the effect of athlete endorser-product relatedness on the audience perception of source credibility in athlete endorsement advertising. An experiment was conducted on a random sample of 60 university students who were instructed to rate their opinion on a scale. The participants were randomized into two groups––a sport-related experimental group and a nonsport-related control group. The results, coinciding with Bartlett’s schema theory, indicate endorser-product relatedness has a significant effect (p < .05) on source credibility in all dimensions—namely, attractiveness, trustworthiness, and expertise. Thus, advertising planners could apply these findings in deciding the choice of endorsers in their advertisement in such a way that they are related. Future researchers can study alternative product or celebrity endorser categories unrelated to sport.